2021
DOI: 10.1371/journal.pone.0256597
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related psychological distress and fears among mothers and pregnant women in Saudi Arabia

Abstract: Objectives This study objectives were to investigate maternal psychological distress, mothers’ fear of their children contracting COVID-19, mothers’ perceptions of the information available regarding children and COVID-19, changes in children’s behavior during lockdown, and concerns of pregnant women in Saudi Arabia. Methods This cross-sectional study surveyed women aged 18 years and older who either had children under 10 years of age or were pregnant at the time of the survey. The outcomes included psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
14
3
Order By: Relevance
“…23 Meraya et al reported higher family income to be inversely associated with psychological distress. 25 However, no association in our study was established between family income and psychological distress. The differences can be due to the study setup, as people related to the health-care profession were the least liable group of people to face financial issues during the pandemic.…”
Section: Discussioncontrasting
confidence: 69%
“…23 Meraya et al reported higher family income to be inversely associated with psychological distress. 25 However, no association in our study was established between family income and psychological distress. The differences can be due to the study setup, as people related to the health-care profession were the least liable group of people to face financial issues during the pandemic.…”
Section: Discussioncontrasting
confidence: 69%
“…Some studies reported that COVID-19 lockdown causes elevated stress and depression in pregnant women ( 5 8 ), but we did not find elevated levels of maternal stress and depression as compared to foreign studies ( 7 , 41 – 43 ) as well as studies conducted in China before the COVID-19 pandemic ( 44 , 45 ). These findings suggest that the citywide lockdown did not significantly increase prenatal stress and depression.…”
Section: Discussioncontrasting
confidence: 99%
“…To slow down and finally end the spread of COVID-19, the Chinese government adopted a measure of lockdown in areas with outbreaks. Previous studies suggested that stress caused by negative events, such as COVID-19 lockdown, can affect vulnerable people, particularly pregnant women ( 4 , 5 ). Data from several countries showed higher levels of maternal stress and more pronounced increases in depression, anxiety, and negative emotions during the COVID-19 pandemic ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding COVID-19 exposures and symptoms, our results suggest that having symptoms and/or confirmed COVID-19 diagnosis were related to anxiety and PTSD only in pregnant women. These results can be explained by concerns about foetal health (Esteban-Gonzalo et al, 2021;Meraya et al, 2021;Mortazavi et al, 2021). In addition, experiencing the death of a close person due to COVID-19 was related to anxiety and depression in postpartum women but not in pregnant women and to PTSD symptoms in both pregnant and postpartum women.…”
Section: Discussionmentioning
confidence: 83%